Role of the Court in Protecting Human Rights in crime-control Model, Accrording to the Criminal Procedure Code of 2015 - Chi, Le Lan (VNU Journal of Science: Legal Studies; Vol 34 No 1DO - 10.25073/2588-1167/vnuls.4139, 2018)
The court exercises the judicial power, thereby plays an important role in protecting human rights. However, such role varies across nations and models of criminal procedure. Vietnam, the country has been following the model of crime control, has its corresponding approach to the role of the court in protecting human rights. Notwithstanding, the current context of improving the rule of law and human rights has posed challenges and raised questions of changing the approach. Keywords The Court, adjudication, human rights, model, due-process, crime-control, the accused References [1] Herbert L. Packer, Two models of the criminal process, University of Pennsylvania Law Review, 1964, 1 ( http://scholarship.law.upenn.edu/penn_law_review/vol113/iss1/1 ) [2] Joycelyn M. Pollock, Ethical Dilemmas and Decisions in Criminal Justice, Cengage Learning, Boston, 2015, p.116 [3] https://www.cliffsnotes.com/study-guides/criminal-justice/the-criminal-justice-system/which-model-crime-control-or-due-process [4] Fairchild, E. and Dammer, H. R., Comparative Criminal Justice System, 2nd ed. Belmont, Wadsworth Thomson Learning, 2001, p. 146 [5] Fairchild, E. and Dammer, H. R., Comparative Criminal Justice System, 2nd ed. Belmont, Wadsworth Thomson Learning, 2001, p. 148 [6] Đào Trí Úc, Hệ thống những nguyên tắc cơ bản của tố tụng hình sự Việt Nam theo Bộ luật tố tụng hình sự năm 2015 (in trong sách chuyên khảo “Những nội dung mới trong Bộ luật tố tụng hình sự năm 2015”, Nguyễn Hoà Bình (chủ biên), Nxb. Chính trị quốc gia – Sự thật, Hà Nội, 2016, trang 59.